Предмет: Математика,
автор: Сергей9класс45школа
Ответы
Автор ответа:
0
х³ + 4х² - 9х - 36 = 0
Преобразуем:
х²(х + 4) - 9(х + 4) = (х² - 9)(х + 4)
(х - 3)(х + 3)(х + 4) = 0
а): х - 3 = 0
х = 3
б): х + 3 = 0
х = -3
в): х + 4 = 0
х = -4
Ответы: -4; -3; 3
Преобразуем:
х²(х + 4) - 9(х + 4) = (х² - 9)(х + 4)
(х - 3)(х + 3)(х + 4) = 0
а): х - 3 = 0
х = 3
б): х + 3 = 0
х = -3
в): х + 4 = 0
х = -4
Ответы: -4; -3; 3
Автор ответа:
0
х²(х + 4) - 9(х + 4) = (х² - 9)(х + 4) Откуда (х² - 9)(х + 4)?
Автор ответа:
0
Там же 0
Автор ответа:
0
Мы просто преобразуем левую часть уравнения
Похожие вопросы
Предмет: Математика,
автор: deragapolina05
Предмет: Математика,
автор: dianaogienko200731
Предмет: Геометрия,
автор: ksusapalcik334
Предмет: Математика,
автор: ppolinna558822005544
Предмет: Математика,
автор: чсапитимесми